Improving quality of experience in wireless voip through novel call scheduling - Lambrinos, Lambros; Τζιούβας, Κώνσταντίνος (My University, 2011)
In the last few years we have experienced a dramatic increase in the use of IP networks for voice applications (VoIP) over wireless networks due to increased bandwidth availability and enhanced device capabilities. Since demand often exceeds available capacity, Call Admission Control mechanisms are in place to prevent the uncontrolled usage of bandwidth. Through the use of an intermediary gateway, VoIP calls are in many cases terminated to a normal landline or cellphone; the capacity of such a gateway is also a finite resource since the number of users can vary significantly as many are mobile. In this article we propose an enhanced scheme that aims to manage access to the lines available so that they are used in a fair manner and utilized to the highest degree possible. This management is facilitated by enhancing a proxy implementation with a number of call scheduling policies. The ability to satisfy pending call requests as soon as lines become available, results in increased user service satisfaction. Moreover, it increases line utilization which is crucial from an economic viewpoint. The ultimate goal is to improve Quality of Experience which is deemed as highly important especially considering that wireless network users experience opportunistic and intermittent connectivity.
Keywords: Call admission control; Call scheduling; Line utilisation; Quality of experience; Quality of service; Voice over IP